Tracing the spatial origins and spread of SARS-CoV-2 Omicron lineages in South Africa - Graeme Dor; Eduan Wilkinson; Darren P. Martin; Monika Moir; Derek Tshiabuila; Dikeledi Kekana; Buhle Ntozini; Rageema Joseph; Arash Iranzadeh; Martin M. Nyaga; Dominique Goedhals; Tongai Maponga; et al. (Nature Communications)
Abstract Since November 2021, five genetically distinct SARS-CoV-2 Omicron lineages (BA.1–BA.5) are believed to have emerged in southern Africa, with four (BA.1, BA.2, BA.4, and BA.5) spreading globally and collectively dominating SARS-CoV-2 diversity. In 2023, BA.2.86, a highly divergent BA.2 lineage that rose to prominence worldwide, was first detected in Israel and Denmark, but the subsequent diversity of South African sequences suggests it too emerged in the region. Using Bayesian phylogeographic inference, we reconstruct the origins and dispersal patterns of BA.1–BA.5 and BA.2.86. Our findings suggest that Gauteng province in South Africa likely played a key role in the emergence and/or amplification of multiple Omicron lineages, though regions with limited sampling may have also contributed. The challenge of precisely tracing these origins highlights the need for broader genomic surveillance across the region to strengthen early detection, track viral evolution, and improve preparedness for future threats.